Responsibilities of Land Deed Drafting Officials (PPAT) for Land Sale and Purchase Deeds that are Canceled with a Sale and Purchase Deed - Widyastuti, Tri; Hafidz, Jawade (Jurnal Konstatering, 2023)
The background for writing this thesis is that the sale and purchase of land is a legal act in the form of surrendering land rights to another party forever (the right to the land is transferred to the party receiving the surrender), this is stated in Article 20 paragraph (2), Article 28 paragraph (3), and Article 35 paragraph (3) of Law Number 5 of 1960 concerning Basic Agrarian Regulations which states that property rights, building use rights can be transferred and transferred. Property rights and building use rights can be transferred by deed made by PPAT. Authority Land Deed Making Officer is a public official who is authorized to make authentic deeds regarding certain legal actions regarding land rights or ownership rights to flat units. Then in the Explanation to Article 45 of Government Regulation number 24 of 1997 concerning Land Registration it is also emphasized that the PPAT Deed is a tool to prove that a legal act has been carried out. The research in writing this thesis is a qualitative research. This research is field research or empirical research with a sociological approach. Characteristics of socio-legal research methods. Socio-legal research is carried out by researching in the field (field research) by interviewing respondents which is primary data and examining library materials which are secondary data and is also called library research. This research aims to analyze or explain the responsibilities of Land Deed Drafting Officials (PPAT) regarding land sale and purchase deeds that are canceled by Sale and Purchase Deeds. The legal action is annulled or annulled, the relevant PPAT deed no longer functions as evidence of the legal action. Therefore, a legal action is canceled by the parties concerned, even though the legal action has been registered at the Land Office, the registration cannot be cancelled. There are two main problems in writing this thesis, namely: What are the legal consequences of the sale and purchase deed made before the Land Deed Making Officer during the registration process at the Agrarian and Spatial Planning/National Land Agency office which is canceled by the sale and purchase deed and the responsibility of the Notary regarding the Sale Deed Purchase that was canceled with a Deed of Sale and Purchase. The results of this thesis research explain how the process of buying and selling land, payments and calculating SSPD BPHTB, is implemented.